Implementation of (AES) Advanced Encryption Standard algorithm in communication application - Moh, Heng Huong (2014)
Internet communication has become more common in this modern world recently, and one of the important algorithms used is ABS algorithm. However, most of the users have inadequate knowledge and understanding regard to this algorithm implementation in the communication field, as well as the level of security and accuracy will be questioned by the users because of the necessary to maintain the confidentiality of particular data transferred. The aim of the thesis is to provide an overview of the ABS encryptiOn algorithm, to develop a prototype that is implemented for communication purpose, and to test the developed prototype in terms of accuracy purpose. The concept of ABS algorithm was firstly studied, including the definition, historical background, and a brief comparison was made between the ABS algorithm with other types of algorithm. Here, the reason of choosing ABS algorithm as the studied was also being explained. A prototype was consequently developed by referring to different sources, with the creation of Graphic Users Interface (GUI) by Java Swing. Fifteen files were then chosen to be the testing materials to examine the level of accuracy and security of the specific developed prototype. The obtained results show the developed prototype was able to encrypt and decrypt the file correctly without making any errors. On the basis of the results of this research, it can be concluded that the developed prototype had high accuracy and security when transferring the file between the sender and receiver that was implemented in client-server application. This research hopes to give a clear idea to the readers about ABS algorithm. Further research about this topic is recommended to increase the efficiency of ABS algorithm implemented in communication field, so that more different types of field can be encrypted and decrypted instead of plaintext.